2002
DOI: 10.1177/002193470203200504
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences among Abused Older African Americans and African American Abusers in an Elder Abuse Provider Agency

Abstract: Objectives of this study were to examine gender differences among mistreated older African Americans and their perpetrators. The analysis was based on substantiated elder abuse cases in Illinois. Gender differences regarding six forms of abuse were examined as were demographic and barrier differences among victims and perpetrators. Overall, older African Americans were more susceptible to financial exploitation and intentional neglect. Other than intentional physical neglect, there were no significant gender d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…Research consistently reveals that the majority of perpetrators of elder abuse and neglect cohabited with their victims (Pritchard, 1992); however, the gender of perpetrators was found to be inconsistent. For example, in several studies, men were more likely to perpetrate elder abuse and neglect (Lithwick, Beaulieu, Gravel, & Straka, 1999; Pritchard, 1992), whereas in other studies, women were more frequently the perpetrators (Dimah, 2001; Dimah & Dimah, 2002; Dunlop, Rothman, Condon, Hebert, & Martinez, 2000).…”
Section: Explaining Elder Abuse and Neglectmentioning
confidence: 99%
“…Research consistently reveals that the majority of perpetrators of elder abuse and neglect cohabited with their victims (Pritchard, 1992); however, the gender of perpetrators was found to be inconsistent. For example, in several studies, men were more likely to perpetrate elder abuse and neglect (Lithwick, Beaulieu, Gravel, & Straka, 1999; Pritchard, 1992), whereas in other studies, women were more frequently the perpetrators (Dimah, 2001; Dimah & Dimah, 2002; Dunlop, Rothman, Condon, Hebert, & Martinez, 2000).…”
Section: Explaining Elder Abuse and Neglectmentioning
confidence: 99%
“…Archer [ 33 ] showed in particular that women often used acts of physical aggression towards their partners, although men inflicted injuries more frequently. A further study [ 34 ] found that females were abusive towards ageing relatives more often than males were (75.0% vs. 67%). Lövestad and Krantz [ 35 ] highlighted that both men and women were victims and perpetrators of physical violence.…”
Section: Introductionmentioning
confidence: 99%
“…A number of articles investigated how differing support systems influenced elder mistreatment risk factors among ethnic/racial groups, again with a primary focus on Asian American and African American elders (Benton, 1999; Brown, 1989; Dimah & Dimah, 2002; Dong, Chang, Wong, & Simon, 2013; Dong, Chen, Fulmer, & Simon, 2014; Griffin & Williams, 1992; Le, 1998; Moon & Benton, 2000; Moon & Evans-Campbell, 2000; Paranjape, Sprauve-Holmes, Gaughan, & Kaslow, 2009; Paulino, 1998; Shellman, 2004; Strumpf, Glicksman, Goldberg-Glen, Fox, & Logue, 2001). A relatively small literature examined prevalence of mistreatment among ethnic/racial groups, either as part of a general population prevalence study (Acierno et al, 2010; Burnes et al, 2015; Laumann et al, 2008) or in ethnic/racially specific samples (Beach, Schulz, Castle, & Rosen, 2010; Buchwald, Tomita, Ashton, Furman, & Manson, 2000; DeLiema, Gassoumis, Homeier, & Wilber, 2012; Dong et al, 2014).…”
Section: Elder Mistreatment and Underserved Groups: What Is Knownmentioning
confidence: 99%